Review of studies on Mandarin language learning motivation from 2011-2020 / Ting Hie-Ling - Ting, Hie-Ling (Universiti Teknologi MARA, Kedah, 2021)
Motivation has been widely accepted by both teachers and researchers as one of the key factors that influence the rate and success of second/ foreign language (L2) learning. This present study provides a systematic review of the research done in Mandarin as second language or foreign language learning motivation published from year 2011-2020 in China. 95 related articles were collected from CNKI database and analyzed based on the five aspects of quantitative overview, types of publication, selection of participants, research methodology and coverage topics. The findings indicated an increment of the published articles from 2011-2015, however starting 2016-2020 the number of published journals show inconsistency. Most of the published articles were empirical studies. Selected respondents were foreign students in China. Majority of the research employed quantitative method in which SPSS was utilized as dominant analysis instrument. The main coverage topics were "types of learning motivation and its causes". It is followed by "learning motivation and learners' differences" and "transition of motivation".